Hybrid solar energy harvesting and storage devices: The promises and challenges. (September 2019) - Lau, D.; Song, N.; Hall, C.; Jiang, Y.; Lim, S.; Perez-Wurfl, I.; Ouyang, Z.; Lennon, A.
Abstract: Hybrid devices that can harvest solar energy and store that energy electrochemically to provide a source of power are increasingly attracting attention due to their potential to provide autonomous power sources. Of particular interest is their ability to support sensors for the Internet of Things (IoT), wearable electronics and autonomous medical monitoring. Many such hybrid devices have been reported, however challenges exist with respect to electrode arrangements and operating modes, form factors, material compatibility and durability. In this perspective, we review both the application potential and design/fabrication challenges for this class of device. It is proposed that device architecture and material choices need to be carefully selected according to the specific intended application to ensure adequate durability and offer practical outcomes over alternative solutions comprising individual solar harvesting and energy storage devices. Graphical abstract: Image 1 Highlights: Solar energy harvesting and storage functionality can be combined in compact hybrid devices. An overview of different device architectures is provided. Hybrid devices can find applications as sensors for IoT, as wearable electronics and in autonomous medical monitoring. Challenges exist with regard to device architecture, material compatibility and durability.